Effects of the COVID-19 Pandemic on Physical Activity in Children: A Systematic Review - Alex Ramirez; Ashley B. Rapp; Sara Santarossa (University Library System, University of Pittsburgh, 2023)
Background: Extended lockdowns established to minimize the spread of COVID-19, may have affected physical activity (PA). The objective of this systematic review was to report how PA of children was impacted by the COVID-19 pandemic. Methods: A database search of CINAHOL, Embase, MEDLINE, PsycInfo, and Web of Science was conducted on 03/29/2021 in accordance with Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Studies were included if they reported a measure of PA for children ≤18 years and were published in English in a peer-reviewed journal. The search generated 673 unique citations. After applying the criteria above, 69 articles were included. The quality of the included articles was assessed using the NIH NHLBI Study Quality Assessment Toolbox. Results: Unstructured play, walking, and virtual PA (e.g., YouTube, online classes) were the most frequently reported modes of PA during the COVID-19 pandemic. The PA of children decreased among 89% of articles that reported changes in PA (e.g., frequency, intensity, duration, or the percentage of children who met PA recommendations) of children during the COVID-19 pandemic. Increased PA was reported more often among younger children, boys, children who lived with other children, and children with more outdoor space. Conclusion: Globally, PA of children decreased during the COVID-19 pandemic. Further work is needed to develop policies to support global PA increases. Limitations of this review include the use of online surveys which are limited by participants ability to recall PA behaviors and access to online resources.